2017
DOI: 10.5539/gjhs.v9n7p96
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Service Quality on Public Health Center and Patient Satisfaction

Abstract: Introduction: The aim of this study was to examine the relationship between services quality on public health center and patient satisfaction in Kutai Kartanegara Regency, Indonesia.Method: This research used pilot pathfinder survey, which was done on February 23 rd -25 th 2017 in Kutai Kartanegara Regency, Indonesia. Two questionnaires were used in the study. During the data collection, there were 192 patients from the health service center, it was consisted two locations representing the urban and rural area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Women and young adults who visit dental and oral health services are more likely than men and elderly. This is in line with previous which finds a large number of female patients visiting dental clinics [1,[12][13][14]. In this study, women presented a high level of satisfaction, a result similar to that previously described [15,16], which suggested that more women taking into account the health and aesthetic conditions of the oral cavity so that more frequent visits to dental and oral health services.…”
Section: Discussionsupporting
confidence: 92%
“…Women and young adults who visit dental and oral health services are more likely than men and elderly. This is in line with previous which finds a large number of female patients visiting dental clinics [1,[12][13][14]. In this study, women presented a high level of satisfaction, a result similar to that previously described [15,16], which suggested that more women taking into account the health and aesthetic conditions of the oral cavity so that more frequent visits to dental and oral health services.…”
Section: Discussionsupporting
confidence: 92%
“…Adults believe they have a higher level of satisfaction with service quality than teenagers because the older the person, the more critical the way they think, and they are able to judge something better. It has been shown previously that patients with age above 45 years was as much as 39.7% [21]. There are only a small number of studies that report the age relationship and patient satisfaction in obtaining care.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the study also revealed that infrastructure has significantly correlated to patient satisfaction. Women want better care, more privacy during visit hours, and less pain [21,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations